2021
DOI: 10.1108/jkm-06-2020-0443
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management within a strategic alliances context: past, present and future

Abstract: Purpose This paper aims at reviewing the extant knowledge management (KM) research field within a strategic alliance context to understand the historical roots, its temporal progression, current state and potential future in a meaningful way. Design/methodology/approach Data for this study was retrieved from the Scopus database using a systematic literature search process. The bibliometric characteristics of 393 research documents were analyzed using bibliometric and structured network analysis. Findings T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 106 publications
(163 reference statements)
0
39
0
2
Order By: Relevance
“…Various bibliometric studies have highlighted the research areas like dynamic capabilities related to internal dynamics, KT, innovativeness and sustainability in IJVs (Aggarwal and Kapoor, 2018; Bamel et al , 2021; Jiatao and Tsui, 2002; White et al , 2016). International firms have been questing for such global economic frameworks for attaining sustainability (Bamel et al , 2021; Roberts and Dörrenbächer, 2016). The study has addressed these specific research gaps of under-investigation of the creation of dynamic capabilities in IJVs by integrating aforementioned research areas (Sapienza et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various bibliometric studies have highlighted the research areas like dynamic capabilities related to internal dynamics, KT, innovativeness and sustainability in IJVs (Aggarwal and Kapoor, 2018; Bamel et al , 2021; Jiatao and Tsui, 2002; White et al , 2016). International firms have been questing for such global economic frameworks for attaining sustainability (Bamel et al , 2021; Roberts and Dörrenbächer, 2016). The study has addressed these specific research gaps of under-investigation of the creation of dynamic capabilities in IJVs by integrating aforementioned research areas (Sapienza et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…KT is a significant issue in IJVs' internal dynamics affecting their survival and success (Griffith et al , 2001). KT is the central theme of knowledge management research that has consistently remained in the limelight (Bamel et al , 2021). Thus, this study has focused on the organizational antecedents, mediator and consequences of KT as per the DCT (Kapoor and Aggarwal, 2020).…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Previous studies also showed that agribusinessmen make their decisions based on a set of economic and noneconomic goals (Barbieri and Mahoney, 2009). However, no studies, to the best of the authors' knowledge, have examined the role of goals in pushing agribusiness diversification under the premises of the resource-based view (RBV), while the RBV is one of the most critical theoretical frameworks which is referred to in the majority of studies in this area (Bamel et al, 2021). Instead, most of the earlier studies relating to behavioral goals encourage diversifications in agritourism (Barbieri and Mahoney, 2009;Hansson et al, 2013) although several past studies also indicated an understanding of the goals or motivations behind entrepreneurial and agricultural diversification (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ashok et al (2021) tacitly declare that the implementation of KM practices enhances service delivery in the public sector. On a similar note, Bamel et al (2020), studies have demonstrated the importance of firm-specific knowledge for the realisation of an organisation's strategy. Contributing to this discourse, Demir et al (2021) contend that good KM practices can specifically increase market share.…”
Section: Organisational Performance In the Construction Sector In South Africamentioning
confidence: 97%